Mouse urinary allergen exposure among animal house workers - Rahman, Nur Badariah Abd (Universiti Sains Malaysia, 2016)
Urine of mice is the main source of allergenic proteins that can enter the human body via inhalation or dermal exposure. The allergens exposure also can spread from one environment to another through airborne dispersal then attach to clothing and skin, and surfaces that in contact. Mus m 1 is a prealbumin and a lipocalin-odorant binding protein with size of 19 kDa and belong to the rodent family of major urinary proteints. The objective of this research is to study the Mus m 1 concentration levels among animal house workers. Mus m 1 were measured from personal and area airborne samples using IOM sampler attached to a sampling pump via tubing for 3 to 8 hours. Wipe sampling was utilised to measure Mus m 1 contamination on hard surface area of workplace using cotton swab. Personal wipe sampling on hands and shoes were collected during pre-, mid- and post-shift. The samples were extracted and analysed using ELISA. Questionnaire enquiring about sociodemographic and job tasks were completed by subjects. Levels of Mus m 1 were significantly higher in mid-shift and post-shift wipes of shoes samples (p = 0.043). There were significant difference of Mus m 1 contamination among mid-shift hands wipe samples (p = 0.01) and mid-shift shoes wipe samples (p = 0.01) between laboratory technicians and office workers. There was also strong significant correlation between midshift among wipe hands and shoes (r = 1.000, p = 0.001). In conclusion, Mus m 1 was detectable in personal and area monitoring of airborne sampling and dermal wipe sampling. Correlation between airborne exposure and dermal had established the potential pathways of Mus m 1 contamination from air to hard surfaces, hard surfaces to dermal and from exposed to non-exposed area.